Polarographic Studies on interaction 2-Aminoquinoxaline with Cd(II) in Aqueous Medium - Pratihar, P.L.; Lohiya, R.K.; Singh, R.V.; Mukherji, S.K. (Asian Journal of Chemistry, 2010)
The effect of ionic concentration of the medium on the complexation has been studied with the help of two different ionic strengths (μ= 0.10 and μ= 0.30) which were maintained by adding requisite quantities of NaCIO4. All other conditions were kept the same at two different ionic strengths. The shift of half wave potentials towards a more negative value with increasing concentration of 2-amino quinoxaline (AQ) indicated complex formation. The diffusion current was found to decrease regularly with the increase of 2-amino quinoxaline concentration.